The effect of walking physical exercise on blood pressure of the pedestrian community in Penjaringan Sari Surabaya - Akmal Zidan Alaudin; Gadis Meinar Sari; Yudi Her Octaviono (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Hypertension is a non-communicable disease that is one of the main causes of premature death in the world. Pharmacologically by administering anti-hypertensive drugs. In non-pharmacological management of hypertension can be done with a healthy lifestyle. A study states that the most appropriate non-pharmacological treatment for people with hypertension is exercise. This research is quantitative research with a quasi-experimental design. The dependent variable in this study was walking physical exercise, while the independent variables in this study consisted of heart rate, systolic blood pressure, and diastolic blood pressure. The subjects of this study were 30 members of the pedestrian community, who were divided by purposive sampling into the treatment group and the control group. The tools used to obtain primary data in this study were the results of measuring blood pressure before and after walking. The results of the study: 1) there is a difference in the average pulse rate between the pretest and post-test in both the treatment and control groups; 2) there is an effect of walking physical exercise on pulse rate; 3) there is a difference in the mean systolic blood pressure and diastolic blood pressure between pretest and post-test; 4) there is a difference in the average blood pressure between the pretest and post-test of the control group; 5) there is no effect of physical exercise walking on blood pressure; 6) There was no difference in blood pressure and pulse between the treatment and control groups. In conclusion, the physical exercise of walking for 1 week could reduce pulse rate but could not reduce systolic blood pressure and diastolic blood pressure.